Immunohistochemical Detection and Molecular Characterization of IDH-mutant Sinonasal Undifferentiated Carcinomas. (August 2018) - Mito, Jeffrey K.; Bishop, Justin A.; Sadow, Peter M.; Stelow, Edward B.; Faquin, William C.; Mills, Stacey E.; Krane, Jeffrey F.; French, Christopher A.; Fletcher, Christopher D.M.; Hornick, Jason L.; Sholl, Lynette M.; Jo, Vickie Y.
Abstract : Recent studies have identified recurrent isocitrate dehydrogenase 2 ( IDH2 ) mutations in a subset of sinonasal undifferentiated carcinomas (SNUCs); however, the true frequency of IDH mutations in SNUC is unknown. We evaluated the utility of mutation-specific IDH1/2 immunohistochemistry (IHC) in a large multi-institutional cohort of SNUC and morphologic mimics. IHC using a multispecific antibody for IDH1/2 (R132/R172) mutant protein was performed on 193 sinonasal tumors including: 53 SNUCs, 8 poorly differentiated carcinomas (PDCARs) and 132 histologic mimics. Mutant IDH1/2 IHC was positive in 26/53 SNUCs (49%; 20 strongly positive and 6 weak) and 3/8 PDCARs (37.5%; 2 strong; 1 weak) but was absent in all other tumor types (0/132). Targeted next-generation sequencing (NGS) on a subset of SNUC/PDCAR (6 strong and 3 weak positive for IDH1/2 IHC; 7 negative) showed frequent IDH2 R172X mutations (10/16) and a single IDH1 R132C mutation. All 6 cases with strong positive mutant IDH1/2 staining and NGS had IDH2 R172S/G mutations. The 3 IHC-weak cases all had IDH2 R172T mutations. Among the 7 tested cases that were negative for mutant IDH1/2 IHC, NGS detected 1 case each with IDH2 R172T and IDH1 R132C mutation. IDH- mutant carcinomas also had frequent mutations in TP53 (55%) and activating mutations in KIT (45%) or the PI3K pathway (36%). Mutation-specific IDH1/2 IHC identifies IDH mutations in SNUC, however, it lacks sensitivity for the full range of IDH mutations. These findings suggest that IDH -mutant sinonasal carcinoma may represent a distinct pathobiological entity with therapeutic implications that can be identified by a combined approach of multispecific IDH1/2 IHC and sequencing. Abstract : Supplemental Digital Content is available in the text.